The candy shop war - Mull, Brandon, 1974- (New York Scholastic, 2007)
When fifth-graders Nate, Summer, Trevor, and Pigeon meet the owner of the new candy store in town and are given a magical candy that endows them with super powers, they find that along with its benefits there are also dangerous consequences.
750
Accelerated Reader AR
Keywords: Magic -- Juvenile fiction; Candy -- Juvenile fiction; Adventure and adventurers -- Juvenile fiction; Friendship -- Juvenile fiction; Fantasy fiction